An empirical formula for predicting the collapse strength of composite cylindrical-shell structures under external pressure loads. (15th January 2019) - Cho, Yoon Sik; Oh, Do Han; Paik, Jeom Kee
Abstract: This paper derives an empirical formula for predicting the collapse strength of composite cylindrical-shell structures under external hydrostatic pressure loads as a function of geometric dimensions and layered angles, where the effects of initial manufacturing imperfections are implicitly taken into account. A series of experiments are undertaken on [ ± θ / 90 ] FW filament-wound-type composite cylindrical-shell models subjected to collapse pressure loads. A total of 20 composite cylindrical-shell models are tested to derive the empirical formula, which is validated by comparison with experimental data, existing design formulas of ASME 2007 and NASA SP-8700, and solutions of the nonlinear finite element method. It is concluded that the proposed formula accurately predicts the collapse pressure loads of filament-wound composite cylinders and will thus aid the safety design of composite cylindrical shell-structures under external pressure loads. Highlights: Derivation of an empirical formula based on the database of testing and FEA. Collapse strength of composite cylindrical-shells. Under external hydrostatic pressure loads. A function of geometric dimensions and layered angles. Effects of initial manufacturing imperfections.